Encapsulation and release of calcein from herceptin-conjugated eLiposomes - Mah Noor Zafar; William G. Pitt; Ghaleb A. Husseini (Heliyon, 2024)
Achieving an optimal therapeutic level is crucial in effectively eradicating cancer cells during treatment. However, conventional chemotherapy-associated systemic administration of anticancer agents leads to many side effects. To achieve the desired control over the target site, active targeting of HER2-positive breast cancer cells can be achieved by conjugating liposomal vesicles with Human Epidermal growth factor Receptor 2 (HER2) and inducing release of the encapsulated drug using ultrasound. To further enhance the delivery efficiency, nanoemulsion droplets exhibiting responsiveness to low-frequency ultrasound are encapsulated within these lipid vesicles. In this study, we prepared four different liposomal formulations, namely pegylated liposomes, emulsion liposomes (eLiposomes), HER-conjugated liposomes, and HER-conjugated eLiposomes, each loaded with calcein and subjected to a thorough characterization process. Their sizes, phospholipid concentration, and amount of antibody conjugation were compared and analyzed. Cryogenic transmission electron microscopy was used to confirm the encapsulation of nanoemulsion droplets within the liposomes. The drug-releasing performance of Herceptin-conjugated eLiposomes was found to surpass that of other liposomal formulations with a notably higher calcein release and established it as a highly effective nanocarrier. The study showcases the efficacy of calcein-loaded and Herceptin-conjugated eLiposomes, which demonstrate rapid and efficient drug release among other liposomal formulations when subjected to ultrasound. This discovery paves the way for a more targeted, efficient, and humane approach to cancer therapy.